Advanced Signature Indexing for Multimedia and Web Applications - Manolopoulos, Yannis; Nanopoulos, Alexandros; Tousidou, Eleni (Advances in Database Systems, 2003)
Advanced Signature Indexing for Multimedia and Web Applications presents the latest research developments in signature-based indexing and query processing, specifically in multimedia and Web domains. These domains now demand a different designation of hashing information in bit-strings (i.e., signatures), and new indexes and query processing methods. The book provides solutions to these issues and addresses the resulting requirements, which are not adequately handled by existing approaches. Examples of these applications include: searching for similar images, representing multi-theme layers in maps, recommending products to Web-clients, and indexing large Web-log files. Special emphasis is given to structure description, implementation techniques and clear evaluation of operations performed (from a performance perspective). Advanced Signature Indexing for Multimedia and Web Applications is an excellent reference for professionals involved in the development of applications in multimedia databases or the Web and may also serve as a textbook for advanced level courses in database and information retrieval systems